Konflik Gender di Pasar Tenaga Kerja Wanita Tani (Studi Fenomenologi Wanita Tani Dalam Membuat Keputusan Kerja) - Anita Kristina; Immamudin Immamudin (Universitas Trunojoyo Madura, 2019)
The purpose of this study is to describe the gender conflict of women farmers in making work decisions. The qualitative approach to phenomenology as the analytical method used in this study. The analysis of this research focuses on women's employment theory and gender. Data was collected through in-depth interviews with female farmers and landowners as well as female family farmers. The results showed that there were gender conflicts when women farmers decided to work, choose jobs, determine the hours of work and determine wages. Gender conflicts occur due to religious values, norms, habits, and reasons that are still inherent and believed by landowners.